Factors influencing students' intention to use mobile learning: A study at Yemen higher education institutions - Basurra, Shuhd Saleh Ali (2021)
Mobile learning (M-learning) is a novel e-learning through mobile technologies. As a result, education for teachers and learners becomes unlimited by time and place. M-learning services makes Yemeni higher education more accessible, but for successful acceptance, students must understand the technology. M-learning implementation in Yemeni higher education institutions are facing two issues namely: the disparity concerning the perceptions of technology between students and the university, and inadequate knowledge and inclusion of students’ acceptance during technology investment decision. The acceptance and use of m-learning services among students in Yemeni higher education is thus examined in this study, and an acceptance model of students of m-learning in higher education environment is proposed banked on Extended Technology Acceptance Model (TAM2). Students’ acceptance of behavior intention to use m-learning and its impact on usage behavior is investigated in higher education environment. Factors such Perceived Ease of Use, Perceived Usefulness, Information Quality and Social Influence have shown a great impact on the Behavior Intention to use Mobile Learning services. This research employed SPSS analysis techniques to test the measurement and structural models with a sample of 381 students.